2011
DOI: 10.1183/09031936.00098411
|View full text |Cite
|
Sign up to set email alerts
|

Treatment failure in pneumonia: impact of antibiotic treatment and cost analysis

Abstract: The aim of this study was to investigate treatment failure (TF) in hospitalised community-acquired pneumonia (CAP) patients with regard to initial antibiotic treatment and economic impact.CAP patients were included in two open, prospective multicentre studies assessing the direct costs for in-patient treatment. Patients received treatment either with moxifloxacin (MFX) or a nonstandardised antibiotic therapy. Any change in antibiotic therapy after .72h of treatment to a broadened antibiotic spectrum was consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
36
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 34 publications
13
36
3
5
Order By: Relevance
“…These expenditures are higher compared to similar studies performed in Germany and Spain (median costs of €1,362 [23], €1,683 [24] and €1,553 [25], respectively), but lower than reported in a study from the United Kingdom (£1,700-5,100, depending on length of stay [7]) and a European study (US$6,530 in a secondary-level hospital in the Netherlands and US$8,444 in a teaching hospital) [26]. The most likely explanation for these discrepancies in hospital costs are expected to be differences in registration, and individual resource item prices.…”
Section: Discussioncontrasting
confidence: 55%
“…These expenditures are higher compared to similar studies performed in Germany and Spain (median costs of €1,362 [23], €1,683 [24] and €1,553 [25], respectively), but lower than reported in a study from the United Kingdom (£1,700-5,100, depending on length of stay [7]) and a European study (US$6,530 in a secondary-level hospital in the Netherlands and US$8,444 in a teaching hospital) [26]. The most likely explanation for these discrepancies in hospital costs are expected to be differences in registration, and individual resource item prices.…”
Section: Discussioncontrasting
confidence: 55%
“…The observation that more early responders had been treated with amoxicillin–clavulanate monotherapy than later responders may be an indication that this treatment is recommended in local hospital guidelines for the treatment of CAP. In a recent study of treatment failure in patients hospitalized with CAP in Switzerland, it was found that those patients who had been treated initially with moxifloxacin or a β-lactam plus macrolide combination experienced lower treatment failure rates and reduced hospital stay, and thus reduced treatment costs, compared with patients receiving β-lactam monotherapy or a non-standardized antibiotic therapy [17]. …”
Section: Discussionmentioning
confidence: 99%
“…12 Clinical treatment failure of patients with pneumonia is associated with increases in overall health care costs, longer hospital LOS, and higher mortality rates. 28,[85][86][87] Oster et al 86 reviewed the clinical and economic consequences of treatment failure in hospitalized patients with CAP and found that failure of initial therapy in these patients was related to significantly higher case fatality rates (8.5% vs 3.3%; P , 0.01), additional days in the hospital (mean ± SD, 10.1 ± 8.1 vs 4.9 ± 3.3 days; P , 0.01), and increased additional hospital charges (mean ± SD, $37 602 ± $71 876 vs $14 371 ± $21 633; P , 0.01) compared with patients who received a successful initial treatment regimen. 86 Delayed effective treatment of patients with pneumonia caused by S. aureus is also associated with high rates of morbidity and mortality and increased hospital costs.…”
Section: Clinical Implications Of Changing Epidemiology and Impact Onmentioning
confidence: 99%